Dog and cat exposures to drugs of abuse identified by the California animal health and food safety laboratory system 2013–2023 - Klainbart, Sigal; Sykes, Chelsea A.; Poppenga, Robert H. (Frontiers in Veterinary Science, 2024)
While known animal exposures to human "drugs of abuse" (DA) were previously considered relatively uncommon in veterinary medicine, the trends are changing. Marijuana and amphetamines are among the 20 toxicants most frequently consulted about with the Pet Poison Helpline. When such exposures occur, they are typically considered emergencies. This retrospective study describes confirmed cases of DA exposure in pets from the California Animal Health and Food Safety Laboratory System (CAHFS). Fifty-seven samples tested positive for DA through liquid chromatography with tandem mass spectrometry analysis (qualitative method). In 75% (43/57) of the DA screen tests, the detected drugs included amphetamine-type stimulants and metabolites (methamphetamine, amphetamine, or both). In 47% (27/57) of cases, a combination of more than one drug group was found. Most cases were diagnosed from a urine specimen. In at least 32% (18/57) of cases, the samples were submitted due to suspicions of animal cruelty, and at least 41% (23/57) of the patients were deceased when the samples were submitted. More studies on the prevalence of illicit drugs in small animals, using confirmatory testing, are warranted to fully understand the significance of this emerging toxicological hazard in veterinary medicine.